Molecular dynamics simulation of the effect of dislocations on the martensitic transformations in a two-dimensional model - Dmitriev, S. V. (2019)
One of the effective ways to study various properties of metallic crystals on atomistic level is molecular dynamics simulation. Even simple Morse or Lennard-Jones interatomic potentials can be used to achieve a qualitative agreement with the experiment. For example, molecular dynamics can be used to study the peculiarities of martensitic transformations - thermodynamics, kinetics, structure, morphology, etc. In this paper, the effect of dislocations on the direct and reverse martensitic transformation is studied by molecular dynamics simulation in a two-dimensional model of the ordered alloy with the AB stoichiometry. The three dimensional analog to this structure is B2 superstructure based on bcc lattice, which is characteristic for intermetallic NiTi alloy. It is found, that the dislocations can be considered as the nucleation centers for martensite phase, increasing the temperature of the direct martensitic transformation in comparison with the homogeneous martensitic transformation. The martensite domains found in the structure after transformation and the reverse martensitic transformation takes place in the presence of the domain boundaries, meaning that the austenite nucleates heterogeneously. At the reverse transformation, splitting of perfect dislocations into partials dislocations took place. Thus, it was established in the present study that, on the one hand, dislocations affect the direct martensitic transformation as the nucleation centers, and from the other hand, reverse martensitic transformation changes the dislocation structure of the modeled alloy.